A Meta-Analysis of the Impact of Game-Based Approaches on Affective and Psychomotor Learning Outcomes in Mathematics Education: Evidence from the Davao Region, Philippines - Orville J. Evardo Jr.; Derren N. Gaylo (Future Science / FSH-PH Publications, 2026)
Although there is a growing interest in the implementation of game-based learning within mathematics education due to its promise of promoting affective and psychomotor learning, research has predominantly concentrated on reported cognitive gains. It is therefore essential to explore further the impact of such approaches on learners in order to ensure that all domains of learning are addressed. The current study therefore aims to synthesise findings from within the Davao Region, Philippines, focusing specifically on affective and psychomotor learner outcomes associated with the use of games. An ex post facto meta-analytic design was used to explore the impact of game-based approaches on affective and psychomotor learner outcomes. A comprehensive search strategy was used to identify relevant published and unpublished quasi-experimental studies that had reported effect sizes pertaining to affective and psychomotor learning from a range of educational settings within the region, including higher education institutions and Department of Education repositories. Four studies met the inclusion criteria, with six effect sizes being incorporated into the analyses. Findings from the meta-analyses revealed a large positive effect associated with the use of games for affective learning, with no studies detected which specifically reported on psychomotor learner outcomes. High levels of between-study variance prompted the use of random-effects models, while no publication bias detected assessed through statistical and graphical techniques.